2021
DOI: 10.1093/schbul/sbab028
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Movement Disorders and Physical Activity in Patients With Schizophrenia: An Actigraphy Study

Abstract: Low physical activity (PA) and sedentary behavior (SB) are major contributors to mental health burden and increased somatic comorbidity and mortality in people with schizophrenia and related psychoses. Movement disorders are highly prevalent in schizophrenia populations and are related to impaired functioning and poor clinical outcome. However, the relationship between movement disorders and PA and SB has remained largely unexplored. Therefore, we aimed to examine the relationship between movement disorders (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 65 publications
3
10
1
Order By: Relevance
“…The three clusters are clinically plausible and may help to define subtypes of the heterogenous SSD syndrome, benefitting future diagnostic efforts. In addition, our results support the phenomenon of co-occurrence of sensorimotor abnormalities described by Walther and colleagues [7] and are also in line with a recent actigraphy study by Pieters and colleagues [57] that showed a significant relationship between parkinsonism and low physical activity and between akathisia and higher physical activity.…”
Section: Discussionsupporting
confidence: 93%
“…The three clusters are clinically plausible and may help to define subtypes of the heterogenous SSD syndrome, benefitting future diagnostic efforts. In addition, our results support the phenomenon of co-occurrence of sensorimotor abnormalities described by Walther and colleagues [7] and are also in line with a recent actigraphy study by Pieters and colleagues [57] that showed a significant relationship between parkinsonism and low physical activity and between akathisia and higher physical activity.…”
Section: Discussionsupporting
confidence: 93%
“…In schizophrenia, associations between physical activity and negative syndrome ( 30 , 31 , 63 ), dosage of antipsychotic medication ( 64 ), and the development of motor activity over the course of schizophrenia ( 65 ) have been investigated. Besides catatonia, actigraphy has been implemented in the investigation of other motor abnormalities such as (antipsychotic-induced) akathisia ( 32 , 66 ), parkinsonism ( 36 , 66 ), dystonia ( 66 ), and restless legs syndrome ( 67 ). Furthermore, psychomotor behaviors in other mental disorders such as major depressive disorder (MDD) have been investigated using actigraphy ( 68 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…25,27,29,30 Furthermore, actigraphy studies in psychosis linked sedentary behavior to illness chronicity, poor cognition, parkinsonism and catatonia. 23,[31][32][33][34] Gait analysis is another instrumental method to assess gross motor behavior, yet limited to the lab setting. For example, gait velocity is reduced in patients with schizophrenia compared to healthy controls (HC).…”
Section: Introductionmentioning
confidence: 99%